Penerapan Penilaian Portofolio untuk Menanamkan Motivasi Belajar Individu Peserta Didik - Magdalena, Ina; Nurchayati, Aan; Dewi, Indria Kusuma (ANWARUL, 2023)
As educators do not only emphasize the cognitive domain, but also the psychomotor and affective domains by getting a balanced portion. A teacher plays an important and primary role for educational purposes. To instill student learning motivation, namely by using and giving direction and learning focus in understanding the benefits of motivation. This study discusses the application of portfolio assessment to instill individual student learning motivation. Portfolio assessment evaluation is divided into process portfolio and product portfolio. The background of this research problem is the lack of students' learning motivation. This research seeks to conduct a systematic review through review articles that are studied from various perspectives and includes qualitative research. The results of this research on the application of portfolio assessment are to instill individual student learning motivation by understanding portfolios, portfolio objectives, benefits of portfolio research, and portfolio research materials. Researchers hope that this research can make students active and foster students' learning motivation so that learning objectives can be achieved optimally.